2015
DOI: 10.1515/ijnaoe-2015-0028
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate uniaxial compressive strength of stiffened panel with opening under lateral pressure

Abstract: This paper concentrated on the ultimate uniaxial compressive strength of stiffened panel with opening under lateral load and also studied the design-oriented formulae. For this purpose, three series of well executed experiments on longitudinal stiffened panel with rectangular opening subjected to the combined load have been selected as test models. The finite element analysis package, ABAQUS, is used for simulation with considering the large elasticplastic deflection behavior of stiffened panels. The feasibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
3
2
0
Order By: Relevance
“…Therefore, this element size was adopted for the spatial discretization of all simulated configurations. The results obtained in the present study and those found by Yu et al [28] are shown in Table 8. The results of Table 8 presented relative differences ranging from 2.71% to 4.51%, ensuring that the proposed computational model can be considered verified.…”
Section: Computational Model Verificationsupporting
confidence: 85%
See 2 more Smart Citations
“…Therefore, this element size was adopted for the spatial discretization of all simulated configurations. The results obtained in the present study and those found by Yu et al [28] are shown in Table 8. The results of Table 8 presented relative differences ranging from 2.71% to 4.51%, ensuring that the proposed computational model can be considered verified.…”
Section: Computational Model Verificationsupporting
confidence: 85%
“…To finish the computational model verification step, the numerical study carried out by Yu et al [28] was reproduced here. To do so, the elastoplastic buckling of a simply supported rectangular stiffened plate with a square centered hole was analyzed, being the structure under uniaxial compression combined with uniform lateral loading.…”
Section: Computational Model Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The present work proposed a computational model to numerically simulate the elasto-plastic buckling of plates due to combined loads, developed using the finite element method in ANSYS® software. The computational model was verified against the works of Kumar, Alagusundaramoorthy and Sundaravadivelu (2009) and Yu, Feng and Chen (2015), with a difference of less than 5% in both comparisons, verifying the proposed model.…”
Section: Discussionsupporting
confidence: 58%
“…Feng and Chen ( 2015) can be seen in Table 2. From Table 2, one can note that the maximum absolute difference is less than 5% compared to Yu, Feng and Chen (2015), verifying the proposed computational model.…”
Section: Verification Of the Computational Modelsupporting
confidence: 60%